Comparison of different electrofusion treatments to be used in rabbit somatic cloning - Cervera, R.P.=700 1 Saeed, A.M.; Silvestre, M.A.; Escriba, M.J.; Garcia-Ximenez, F.
(Es, En)
ilus., 29 ref.
Keywords: CLONACION; FIBROBLASTOS; CELULAS; CONEJO (ORYCTOLAGUS); ESPAÑA; CLONACION SOMATICA; ELECTROFUSION; OSMOLARIDAD